2020
DOI: 10.23736/s0022-4707.20.10312-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise in high-humidity on heart rate variability and salivary oxidative stress in obese and lightweight asthmatic children

Abstract: Background: Asthma and obesity are becoming increasingly common among children. Such conditions are known to negatively affect both cardiac autonomic function and oxidative stress. We therefore investigated the heart rate variability (HRV) and oxidative (malondialdehyde, MDA) response to exercise within a high humidity environment (~65%) in obese and lightweight asthmatic children.Methods: Forty-two children participated in this study and were categorized into four groups: obese asthmatic (OA, n = 10), obese n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 38 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…In addition, 2 of the 4 studies found 5,12 demonstrated lower SDNN values in the asthma group. Regarding RMSSD, 5 of 6 studies 3,6,12,14,25 found higher values in the asthma group; only Rimes et al 26 found a lower value in the asthma group. As for frequency‐domain variables, 6 of 8 studies 4,12,15,25,28,29 found higher HF values in the asthma group; only Kazuma et al 5 and Rimes et al 26 found lower values in the asthma group.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, 2 of the 4 studies found 5,12 demonstrated lower SDNN values in the asthma group. Regarding RMSSD, 5 of 6 studies 3,6,12,14,25 found higher values in the asthma group; only Rimes et al 26 found a lower value in the asthma group. As for frequency‐domain variables, 6 of 8 studies 4,12,15,25,28,29 found higher HF values in the asthma group; only Kazuma et al 5 and Rimes et al 26 found lower values in the asthma group.…”
Section: Resultsmentioning
confidence: 94%
“…Ten studies 3,4,6,14–16,24–26,28 assessed HRV using short‐term recordings (ranging from 10 s to 10 min), and 4 5,12,13,29 used long‐term measurements (24 h). Regarding HRV software, 4 studies 4,14,16,24 used Kubios HRV. The main HRV variables included R‐R, SDNN, RMSSD, pNN50, LF, HF, LF/HF, SD1 and SD2 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is limited research investigating the impact of physical activity interventions on childhood obesity-associated oxidative stress ( Table 1.2B ), acute aerobic cycling exercise seems to exert contrary effects on oxidative markers in obese children. Specifically, Ahmadian et al ( 70 ) reported a decrease in MDA levels after an acute progressive test until volitional exhaustion in both obese and normal-weight children under the age of 13 years, as well as in their asthmatic counterparts ( 70 ), Paltoglou et al ( 71 ) reported an increase in the levels of TBARS and protein carbonyls (PCs), as well as in TAC, and catalase, along with a decrease in the production of GSH and GSH/GSSG in both prepubertal and pubertal obese children following an acute bout of maximal aerobic exercise. These responses to acute aerobic exercise were also observed in their prepubertal and pubertal normal-weight counterparts.…”
Section: Childhood Obesity: Oxidative Stress Status and Benefits Of E...mentioning
confidence: 99%